Relevansi Konsep Tarbiyah Islamiyah Terhadap Pendidikan Anak Usia Dini Di Era Society 5.0 - Muhtarom; Reliska; Ocha Nopriana; Amelia; Rahayu; Intan Permata Sari; Annisa Haryanto (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2026)
The rapid penetration of cyber-physical technology in the Society 5.0 era has triggered a crisis of moral degradation, gadget dependency, and the fading of humanistic-religious values in early childhood. This study aims to analyze the conceptual-philosophical relevance of Tarbiyah Islamiyah to the philosophical foundations of contemporary Early Childhood Education (ECE) and to formulate an internalization model to protect children's morality. The research method used is library research with a qualitative-descriptive approach. Data collection was carried out through structured digital documentation from authoritative literature and reputable journal articles over the last five years (2022–2026). A data categorization matrix was utilized as the research instrument, while data analysis applied the content analysis model integrated with educational hermeneutics techniques. The results indicate that Tarbiyah Islamiyah has a robust epistemological relevance in shaping a fitrah-friendly ECE ecosystem in the digital era. The success of this relevance is realized through an integrated model that aligns the aspects of tarbiyah jasmaniyah (screen time regulation), tarbiyah fikriyah (critical-reflective digital literacy), and tarbiyah khuluqiyah (instilling cyber adab/digital akhlak based on exemplary behavior). However, practical implementation in the field is still constrained by the gap in digital competence among educators. This study contributes a theoretical-applicative guide for teachers and parents in steering children's emotional-social intelligence amidst cyber disruption.